ANALISIS PENGARUH BRAND EXTENSION TERHADAP MINAT BELI PRODUK HUGGIES PADA KONSUMEN IBU RUMAH TANGGA - Aldo Saputra (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
The business world is now experiencing rapid growth, as well as the growing population. The challenge facing marketers today is how to have a great marketing strategy. One of the marketing strategies undertaken by PT. Kimberly Clark is a brand extension. The purpose of this research is to examine the variable of brand extension that influence to buying interest, which is done by using the component of brand extension that is: 1) Similarity or similarity with the product of origin, 2) Reputation or ability owned by company to increase the value of society or consumer, 3) Perceived quality or consumer judgment about the superiority of a product, 4) Innovativeness is the ideas the company spends on creating new services and products. Data analysis used in this research is through multiple linear regression analysis method. The results showed that 200 respondents consumers of housewives are not interested to buy Huggies brand extension products. he results show that the interest in purchasing Huggies extension product is not affected by similarity, reputation, perceived quality, and innovativeness